2012
DOI: 10.1002/ccd.24367
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical outcome of rotational atherectomy followed by drug‐eluting stent implantation in complex calcified coronary lesions

Abstract: This study represents the largest European data set of patients treated with RA in the DES era. RA followed by DES implantation in calcified coronary lesions appears to be feasible and effective, with a high rate of procedural success and low incidence of TLR and MACE at long term considering this complex patient and lesion subset.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
76
4

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 116 publications
(103 citation statements)
references
References 22 publications
(24 reference statements)
13
76
4
Order By: Relevance
“…On the other hand, we have also proven that long‐term FU of our high‐risk, elderly RA stented patients yield acceptable all‐cause mortality data as compared with that in other databases 1, 2, 3, 4, 5, 6.…”
Section: Discussionmentioning
confidence: 51%
See 4 more Smart Citations
“…On the other hand, we have also proven that long‐term FU of our high‐risk, elderly RA stented patients yield acceptable all‐cause mortality data as compared with that in other databases 1, 2, 3, 4, 5, 6.…”
Section: Discussionmentioning
confidence: 51%
“…Benezet et al 1 published total cardiac death, target lesion revascularization, and MI incidence rates of up to 4.9%, 3.9%, and 8.8%, respectively, at 15 months FU with RA stenting using DES devices. Abdel‐Wahab et al 2 also found promising long‐term results following RA stenting with DES systems in a large patient database. Despite all these promising trials, however, ACS and high‐risk patients were either excluded from different studies or were not sufficiently examined.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations